City, state and citizenship in South Africa: towards a normative approach - Atkinson, Doreen (My University, 1991)
South African historiography is ripe for change. Since the emergence of revisionism in the 1960s, South African politics has been studied using certain hitherto unquestioned assumptions. The radical paradigm has been responsible for extraordinary insights in South African political and historical analysis; however, also it needs to be transcended in important ways. It is the aim of this paper to subject these assumptions to critical scrutiny, and to develop an alternative approach to the study of political phenomena in South Africa - an approach from the perspective of Apolitical morality'. To some extent, I will have to overstate my case - most notably by underplaying the important dynamics of conflict and coercion. I feel this is legitimate however, because these issues have occupied, unchallenged, the centre stage in political analysis in this country. After a review of the existing literature and some theoretical comments, I will apply the notion of Apolitical morality' to a specific historical context, viz. township administration in South African cities during the 1950s.
African Studies Seminar series. Paper presented 2nd September, 1991
Keywords: Ideology. South Africa; Political change. South Africa; South Africa. Politics